1998
DOI: 10.1046/j.1469-8137.1998.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of an early successional plant community as influenced by ozone

Abstract: An early successional plant community was exposed to various ozone concentrations for two growing seasons (1994)(1995) in open-top chambers in Auburn, Alabama, USA. The ozone treatments were : AA, ambient air (open plots) ; CF, carbon-filtered air (c. 0n5iambient air), 1i, non-filtered air, and 2i, twice ambient air. Vegetative canopy cover exhibited a pattern of accumulation in the spring, with maximum canopy cover attained in summer, then senescence of foliage in the autumn 1994. This pattern was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…There is nothing known about the rate of recovery of sensitive species in low-ozone periods (Fuhrer, 1997). Duchelle et al, (1983), Evans & Ashmore (1992), Barbo et al (1994), Ashmore et al, (1995) and Barbo et al (1998) have all used OTCs placed over natural vegetation. Duchelle et al, (1983) determined the effects of ozone on the productivity of natural vegetation in a high meadow in the Shenandoah National Park, USA.…”
Section: Competition and Managed Grasslandsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is nothing known about the rate of recovery of sensitive species in low-ozone periods (Fuhrer, 1997). Duchelle et al, (1983), Evans & Ashmore (1992), Barbo et al (1994), Ashmore et al, (1995) and Barbo et al (1998) have all used OTCs placed over natural vegetation. Duchelle et al, (1983) determined the effects of ozone on the productivity of natural vegetation in a high meadow in the Shenandoah National Park, USA.…”
Section: Competition and Managed Grasslandsmentioning
confidence: 99%
“…Unfortunately no data on species composition were reported. Working a little further south, Barbo et al, (1994), and Barbo et al (1998), exposed an early successional forest community to AA, CF, NF and 2iAA. They found changes in species performance, canopy structure, species richness, diversity index and evenness (Fig.…”
Section: Competition and Managed Grasslandsmentioning
confidence: 99%
“…The more ozone-sensitive species also tended to have a higher genetic multiplicity and diversity . Indeed, Barbo et al (1998) showed that in an early successional plant community, exposure to ozone led to a less complex community structure by affecting competitive interactions among plants.…”
Section: Percy Et Al 2003)mentioning
confidence: 99%
“…Semi-natural vegetation is frequently exposed to elevated ozone (0 3 ) concentrations throughout Europe (EMEP, 2002) which can adversely affect the most sensitive species, inducing changes in the floristic composition of plant communities (Ashmore and Ainsworth, 1995;Barbo et al, 1998;Fuhrer et al, 1994). However, limited information has been provided regarding the sensitivity of these ecosystems to 0 3 as has been recently reported in the last UN/ECE (United Nations Economic Commission for Europe) workshop held to define ozone critical levels for plant protection (Ashmore and Franzaring, 2003).…”
Section: Introductionmentioning
confidence: 99%